2011
DOI: 10.1038/ajg.2011.119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of On-Site Cytopathology Evaluation on the Diagnostic Accuracy of Endoscopic Ultrasound-Guided Fine Needle Aspiration (EUS-FNA) of Solid Pancreatic Masses

Abstract: On-site cytopathological evaluation improves the diagnostic yield of EUS-guided FNA for the cytological diagnosis of solid pancreatic masses. This is associated with a significantly lower number of inadequate samples and a lower number of needle passes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
251
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(262 citation statements)
references
References 39 publications
6
251
0
5
Order By: Relevance
“…Without on-site evaluation, the recommended number of passes is 5-7 for solid pancreatic lesions and 2-3 for lymph nodes (34,40,41). However, the on-site pathologist allows reducing the number of needle passes and increasing the diagnostic accuracy of the EUS-guided FNA (42). For pancreatic tumors, additional needles and punctures are needed in 15 % of cases, increasing the overall procedural time (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without on-site evaluation, the recommended number of passes is 5-7 for solid pancreatic lesions and 2-3 for lymph nodes (34,40,41). However, the on-site pathologist allows reducing the number of needle passes and increasing the diagnostic accuracy of the EUS-guided FNA (42). For pancreatic tumors, additional needles and punctures are needed in 15 % of cases, increasing the overall procedural time (9).…”
Section: Discussionmentioning
confidence: 99%
“…Conventional EUS-FNA has certain limitations. Sensitivity significantly decreases by 10-15 % without an on-site pathologist to evaluate the sample obtained during the procedure (40)(41)(42). Without on-site evaluation, the recommended number of passes is 5-7 for solid pancreatic lesions and 2-3 for lymph nodes (34,40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Reported sensitivity and accuracy for malignancy ranges from 75 to 92% and from 79 to 92%, respectively (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). This accuracy may be even higher using on-site evaluation of the sample by an experienced pathologist (34). Furthermore, in addition to differentiation between benign and malignant lesions, EUS-FNA can also establish the final diagnosis in many cases (33).…”
Section: Introductionmentioning
confidence: 99%
“…Klapman et al (10) showed that with ROSE performed by a pathologist, only 23% of aspirates had inconclusive cytological diagnosis, whereas the number of inconclusive aspirates increased to 48% when ROSE was not available. Many other studies have shown significant increase by as much as 90% in the diagnostic yield of radiologically guided FNACs with the application of ROSE by a cytopathologist (11)(12)(13)(14). In our study, the diagnostic yield of radiologically guided hepatic FNACs increased up to 95.8% when ROSE was applied (2015-2016) compared with 86.25% when ROSE was not applied (2011)(2012)(2013), which proved to be a statistically significant improvement.…”
Section: -2016mentioning
confidence: 99%